Lower corrosion resistance of the nitrocarburized layer formed on two supermartensitic stainless steel types - Rodrigues, Cesar Augusto Duarte; Casteletti, Luiz Carlos; Fernandes, Frederico Augusto Pires; Picon, Carlos Alberto [UNESP]; Tremiliosi-Filho, Germano (FapUNIFESP (SciELO), 2024)
The aim of this study was to verify the pitting corrosion behavior in the surface layers obtained by plasma nitrocarburizing at 400 and 450 °C/5 h on two types of super-martensitic stainless steel, namely micro-alloyed (Nb-SMSS) and unalloyed (SMSS). The results reveal that in all the nitrocarburized layers, a discontinuous, thin layer measuring less than 5µm in thickness exhibits a microhardness exceeding 950 HV0.05, for the two steels. Furthermore, the structure of the surface layer is a combination of expanded austenite (γN), expanded martensite (α`N), ε-Fe2-3 N, cementite (θ-Fe3 C), and traces of CrN. The surfaces exhibit poor corrosion resistance across all layers, which can be attributed to localized micro-galvanic corrosion between the iron nitride (ε-Fe2-3 N) and expanded austenite (γN), since they are known to have higher corrosion resistance, as well as expanded martensite ((α`N) and cementite (θ-Fe3 C), which have lower corrosion resistance. This corrosion process initiates after the dissolution of the surface layer in a 3.5% NaCl solution, subsequently leading to substrate corrosion.
Keywords: hardness; microstructure; niobium; pitting corrosion resistance; plasma nitrocarburizing; super-martensitic stainless steel